E-Procurement System and Adoption for SMEs - VAYVAY, ÖZALP (IGI GLOBAL, 2011)
An electronic procurement (e-procurement) system is an electronic based procurement style that facilitates effective communications along the entire supply chain. E-procurement accelerates SMEs (small and medium size enterprises) at a reduced cost. The purpose of this chapter is to show that adoption of an e-procurement system is essential in the supply chain for SMEs and to find solutions in order to make using this system as easy as possible. The adoption should be considered as a re-engineering process from an innovative perspective. An adoption plan is proposed within the study. It contains three phases: 1) identification of the e-procurement process, 2) seeking integration points with other elements of the system, and 3) IT implementation of the integration areas. The study also proposes to use business process management tools that have workflow engines and Web service implementations for integration points. Although BPM (business process management) tools are seen as quite expensive to SMEs, there are also dependable free licensed ones. The study is concluded with a case-study that is implemented with a free-licensed BPM tool for proof-of-concepts.